Platelet Aggregation and Serotonin Release, Coagulation, Fibrinolysis, Antiplasmin, Factor XIII, and Antithrombin III in Acute Transmural Non+Complicated Myo-Cardial Infarction - Bjerre Knudsen, J.; Amtorp, O.; Skagen, K.; Gormsen, J. (Thrombosis and Haemostasis, 1979)
Platelet aggregation in vitro (ADP and adrenalin). Serotonin release, APTT, Factor VIII, Factor XIII, FE-a, plasma ethanol gelation teat, euglobulinclotlysiatime, antiplaeain and antithrombin III were estimated in 12 patients with acute transmural nob-complicated myocardial infarctions receiving no drugs with any known influence on the actual parameters. Distinct, uniform, changes were round. Initially distinct decrease in aggregation and release was present, changing within a week into increased aggregability, as estimated by threshold concentrations, and increased release function. The platelets remained “hyperactive” in above 50% at the discharge. Positive gelation test appeared after 1-2 days with peak level day 5, became afterwards negative in all. The fibrinolytic activity was within normal range day 1-2. It decreased rapidly with lowest activity on day 5-6 contemporarily with a peak activity of antiplasmin. Afterwards it increased slowly, but was still low in around 50% at the discharge. Factor VIII activity increased significantly with peak day 5-6. Factor XIII decreased biologically with lowest activity on day 5-6, increased to normal levels, Antithrombin III remained unchanged, in upper part of normal range. Thus, changes in platelet patterns are demonstrable at the onset of the infarction, while the other parameters develop later.